Ablation of Matrix Metalloproteinase-9 Prevents Cardiomyocytes Contractile Dysfunction in Diabetics - Prathipati, Priyanka; Metreveli, Naira; Nandi, Shyam Sundar; Tyagi, Suresh C.; Mishra, Paras K. (Frontiers in Physiology, 2016)
Elevated expression and activity of matrix metalloproteinase-9 (MMP9) and decreased contractility of cardiomyocytes are documented in diabetic hearts. However, it is unclear whether MMP is involved in the regulation of contractility of cardiomyocytes in diabetic hearts. In the present study, we tested the hypothesis that MMP9 regulates contractility of cardiomyocytes in diabetic hearts, and ablation of matrix metalloproteinase-9 (MMP9) prevents impaired contractility of cardiomyocytes in diabetic hearts. To determine the specific role of MMP9 in cardiomyocyte contractility, we used twelve - fourteen week male WT (normoglycemic sibling of Akita), Akita, and Ins2+/- /MMP9-/- (DKO) mice. DKO mice were generated by cross-breeding male Ins2+/- Akita (T1D) with female MMP9 knockout (MMP9-/-) mice. We isolated cardiomyocytes from the heart of the above three groups of mice and measured their contractility and calcium transients. Moreover, we determined mRNA and protein levels of sarco-endoplasmic reticulum calcium ATPase-2a (SERCA-2a), which is involved in calcium handling during contractility of cardiomyocytes, in WT, Akita, and DKO hearts using qPCR, Western blotting and immunoprecipitation, respectively. Our results revealed that in Akita hearts where increased expression and activity of MMP9 is reported, the rates of shortening and re-lengthening (± dL/dt) of cardiomyocytes were decreased, time to 90% peak height and baseline during contractility was increased, rate of calcium decay was increased, and calcium transient was decreased as compared to WT cardiomyocytes. However, these changes in Akita were blunted in DKO cardiomyocytes. The molecular analyses of SERCA-2a in the hearts showed that it was downregulated in Akita as compared to WT but was comparatively upregulated in DKO. These results suggest that abrogation of MMP9 gene prevents contractility of cardiomyocytes, possibly by increasing SERCA-2a and calcium transients. We conclude that MMP9 plays crucial role in the regulation of contractility of cardiomyocytes in diabetic hearts.